Energy-Efficient Communication Processors Design and Implementation for Emerging Wireless Systems - Fasthuber, Robert; Catthoor, Francky; Raghavan, Praveen; Naessens, Frederik; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
This book describes a new design approach for energy-efficient, Domain-Specific Instruction set Processor (DSIP) architectures for the wireless baseband domain. The innovative techniques presented enable co-design of algorithms, architectures and technology, for efficient implementation of the most advanced technologies. To demonstrate the feasibility of the author$1 (Bs design approach, case studies are included for crucial functionality of advanced wireless systems with increased computational performance, flexibility and reusability. Designers using this approach will benefit from reduced development/product costs and greater scalability to future process technology nodes. Describes a DSIP architecture explicitly for the wireless domain, significantly more efficient than methods commonly in use; Includes an efficient DSIP architecture template, which can be reused for specific designs; Uses holistic design approach, considering all relevant requirements and combining many innovative/disruptive design concepts; Enables design portability, given changing target devices.s
Context and State-of-the-Art -- Processor Template for the Wireless Domain -- Case Study 1: MIMO Detector -- Case Study 2: FIR Filter -- Case study 3: FFT -- Front-End Design for the Processor Template -- Back-End Design for the Processor Template.
Keywords: Engineering; Microprocessors; Electronics; Microelectronics; Electronic circuits; Engineering; Circuits and Systems; Processor Architectures; Electronics and Microelectronics, Instrumentation; Electronic books